Novel malformations: Chiari type 1 and hydrocephalus in Zhu‐Tokita‐Takenouchi‐Kim syndrome and novel SON variants. Issue 12 (15th December 2022) - Pavone, Piero; Saia, Federica; Pappalardo, Xena; Barbagallo, Massimo; Prato, Adriana; Rizzo, Renata
Abstract: Zhu‐Tokita‐Tachenouchi‐Kim syndrome (ZTTK) is a recently recognized malformation syndrome presenting with craniofacial dysmorphism, developmental delay/intellectual disability, seizures, anomalies involving brain white matter, and other body‐organs. In humans, the disorder is linked to the loss‐of‐function variants in the SON gene (MIM# 617140). Herewith, a new case of this syndrome is reported in a 2‐year‐old Caucasian child who presented the classical clinical features of the ZTTK syndrome in association with hydrocephalus and Chiari malformations type 1 an anomaly previously unreported. Exome analysis showed a de novo heterozygous variant in SON gene. Literature review of similar cases is reported. Abstract : Zhu‐Tokita‐Tachenouchi‐Kim syndrome (ZTTK) is a severe malformation syndrome characterized by craniofacial dysmorphism, developmental delay/intellectual disability, seizures, anomalies involving brain white matter, and other body‐organs. The disorder is linked to the loss‐of‐function variants in the SON gene (MIM# 617140).